Skid Resistance and Texture Depth Analysis of Stone Mastic Asphalt - Mohamed, Abdullahi Ali (2001)
The skid resistance of highway pavements, particularly when wet, is a serious problem. As traffic speeds and densities continue to rise, the chances of skidding accidents as well as their consequences are both growing at an alarming rate with each passing year. Skid resistance between tire and road surface is a function of contact area. Maximum grip may be generated in dry conditions while in wet conditions the presence of surface water on the road surface may reduce the contact area and consequently reduce the available grip. Since 1994, Universiti Putra Malaysia had been involved in Stone Mastic Asphalt (SMA) Technology research, to formulate for Malaysian roads, SMA, presents a very uniformly textured surface that can achieve grip or friction between rubber tire and road surface. In this study, pavement surface interaction was given the highest priority, and slab specimens were prepared by varying gradation of SMA 14 to simulate the actual behavior of field skid resistance. Conventional hot mix asphalt was also prepared as a control. The results of skid resistance and texture depth were tabulated with the variables (Angularity Number, Particle Index, and Percentage of Asphalt, Voids in Total Mix, Voids in Mineral Aggregate, Distribution of Coarse Aggregate and Polished Stone Value). Statistical analyses were performed to assess the relationship between physical and mechanical properties of the mix, and to study how the mixing materials contribute to the skid resistance and the texture depth of SMA. SPSS and EXCEL packages were employed to investigate these relationships. The foregoing data indicate convincingly that Angularity Number as measured by the angularity test, had highly significant effects on the skid resistance of SMA. In this case, the British Portable Number is shown to increase with increasing value of angularity number. For coarse aggregate and percentage of asphalt has significant effect P<O.05 on texture depth. It was also noted that the data of skid resistance and texture depth indicated a wide spread of values obtained ranging from SMA 14 ranging 93 up to 124 BPN units, regardless of composition of the mixture. It may therefore be concluded that SMA has the potential to optimize the contact area between tires and road surface under dry and wet surface conditions.